Customer Satisfaction's Influence on Repurchase Intention in Indonesia's E-commerce Sector - Afinia, Shevila; Tjahjaningsih, Endang (SAFE-Network, 2024)
The rapid growth of e-commerce in Indonesia has significantly impacted the digital economy, becoming a vital driver of economic development. With increasing competition, maintaining customer satisfaction is essential for online platforms' success. This study explores the relationship between customer satisfaction and repurchase intention within Indonesian e-commerce. It aims to understand how satisfaction influences customers' likelihood to repurchase products or services. A quantitative approach was used, involving 90 respondents in Semarang, selected via purposive sampling. Data were collected through structured questionnaires with Likert scales to gauge customer responses. Statistical analysis, including validity testing and multiple linear regression, was conducted using SPSS software to examine the relationships among customer satisfaction, trust, electronic word-of-mouth, and repurchase intention. The results demonstrate a significant positive relationship between customer satisfaction and repurchase intention. Statistical tests showed that both satisfaction and trust significantly impact repurchase intention, with p-values of 0.023 and 0.019, respectively. The study also confirmed the validity and reliability of the measurement instruments. In conclusion, the findings underscore the importance of prioritizing customer satisfaction to enhance loyalty and encourage repeat purchases. Indonesian e-commerce platforms should focus on building trust, delivering quality service, and fostering positive customer experiences to increase repurchase intention and sustain long-term success.